Estimating Characteristics of the Foreign-Born by Legal Status - Judson, Dean H. author. aut Link
IV, 70 p. 2 illus.
Keywords: This brief represents a comprehensive review of methods for estimating characteristics of the foreign-born population in the United States, specifically oriented toward characteristics by legal status. A variety of methods have been proffered over the past many decades, in a large variety of venues; this work brings them together, attempts to impart some order on the definition of “legal status,” and describes strengths and deficiencies both in methods and in data. The authors have a combined 50 years of experience in both demographic and statistical methodology.